POTENSI NETRALISASI IMUNOGLOBULIN Y ANTITETANUS YANG DIISOLASI DARI TELUR AYAM (THE POTENCY NETRALIZATION OF ANTI TETANUS IMMUNOGLOBULIN Y THAT WERE ISOLATED FROM CHICKEN EGGS) - Suartha, I Nyoman; Teguh Wibawan, I Wayan; Damayanti Soejoedono, Retno; W. Lay, Bibiana (Jurnal Veteriner; Vol 8 No 2 (2007))
The porpuse of study was to explore the potential use of? anti tetanus IgY from eggs yolk as a substitute for anti tetanus serum raised in ?horses. The eggs were collected from chickens which have previously been immunized with tetanus toxoid. Neutralization potency test of anti tetanus IgY determined by ? Spearman-Karber method.? The highest mean titer of anti tetanus of egg yolk was 80.16 ? 33.55 IU/ml and the lowest was 1.69 ? 0.63 IU/ml. The concentration? of purified IgY was 1.644 ? 0.424 mg/ml.  Spearman-Karber value of potency of anti tetanus IgY are 35 IU/ml.  ? This research concluded that Chickens was capable of produced of anti tetanus in eggs yolk with value of potency are 35 IU/ml.
Keywords: mmunoglobulin Y, chicken, antitetanus serum, potency